How to Control the House Prices Through the Demand Sides? - Shochrul Rohmatul Ajija, - (Faculty of Economics, University of Tehran, 2023)
This study aims to examine and analyze the factors, which influence house prices from the demand side in developed and developing countries. It was tested using the Generalized Method of Moments with the dependent and the independent variable of the house price index involving real interest rates, credit, economic, and population growth. This study uses 54 panel data which is divided into 31 sub-groups of developed countries and 23 developing countries from 2005 to 2017. This research tries to contribute in observing the role of macroprudential and monetary policies in controlling housing prices globally in both developed and emerging markets as well as looking for the relationship between credit growth and house prices because credit is the closest macroprudential and monetary policy channel to the real sector. The results showed that interest rates, credit, economic, and population growth significantly effect housing prices. Interest rate variables have a negative effect, while credit, economic growth, and population growth have a positive effect on house prices. The influence coefficient's magnitude is different from developed countries to have a more significant influence than developing countries. Another result show that improvement of house price index caused by credit growth enhancement in developed countries greater than in developing countries. Furthermore, the study provides suggestions for policymakers to control house prices due to a reduction, which causes financial crisis. Therefore, the government needs to enter into financial institutions to increase prudence in the housing finance system.